RETRACTED: Renewable energy incentives on the road to sustainable development during climate change: A review - Tryndina, Nicole; An, Jaehyung; Varyash, Igor; Litvishko, Oleg; Khomyakova, Lyubov; Barykin, Sergey; Kalinina, Olga (Frontiers in Environmental Science, 2022)
This review is dedicated to the analytical literature concerning the dynamics of different approaches to renewable energy promotion. The examples of major types of green energy incentives, including carbon tax, Feed-in Tariffs, investment in Research and Development have been covered in the paper, as well as the barriers and limitations of such practices, and the contradictions existing in the field of renewable energy. The dynamics of chosen ways of green energy promotion over defined period have been addressed. This review aims at assessing energy consideration and importance of raising public awareness on the issue have been analyzed. The evidence, collected through the literature analysis, has proved that despite of a significant amount of work done in the field of the transition to the renewable energy sources, including implementation of various incentives, there are still controversial aspects which demand attention both from economists as well as from policymakers. Modern best practices in the field of green energy incentives can be based on government initiative or stem from the private sector. The most widely used policies for renewable energy promotion as was revealed in the reviewed studies are tax incentives, however, at the same time numerous countries provide fossil fuels subsidies to minimize the level of inequality. Finally, the outlook of different practices concerning financing of the transition from traditional energy sources to renewable ones have been presented.